Vietnamese-English Bilingualism: Patterns of Code-Switching, 1st edition - Ho, Dac Tuc (Routledge, 2020)
This book is concerned with three central issues: the universality of constraints on code-switching, the nature of the relation between language contact and bilingualism, and the social and linguistic components that facilitate code-switching.